Melatonin Modulates the Phytochelatin Synthase and Glutathione Synthase Gene Expression and the Antioxidant Performance of Soybean Plants Under Cadmium Stress - Hakimeh Oloumi; Mahmood Maleki (International Journal of Agronomy)
This study examines the regulatory impact of melatonin (MT) on soybean (Glycine max) under cadmium-induced stress. The experiment followed a completely randomized factorial design with three replications, conducted under greenhouse conditions. Treatments included MT at 0 μM (control) and 50 μM (optimized level), along with cadmium chloride at 0 μM (control), 50 μM (moderate stress), and 100 μM (severe stress). Various physiological, biochemical, and molecular parameters were assessed, including antioxidant activity, glutathione synthase (GS) and phytochelatin synthase (PCS) gene expression, and developmental traits. MT notably improved root elongation and the root-to-shoot ratio under cadmium stress but did not significantly affect photosynthetic pigment levels. However, MT treatment enhanced relative water content (RWC), protein, and phenolic compound accumulation under severe cadmium exposure. The activity of antioxidant enzymes and hydrogen peroxide (H2O2) production exhibited distinct patterns in response to MT treatment under 50 μM and 100 μM Cd stress. MT reduced H2O2 levels by modulating APX, GPX, and CAT activities. This study is the first to reveal that MT mitigates cadmium-induced stress by regulating GS and PCS gene expression in soybean. Specifically, MT upregulated GS419 while downregulating HGS, GS473, and GS288 under 50 μM Cd. Additionally, MT application exhibited a synergistic effect in enhancing PCS gene expression, indicating a protective role against cadmium toxicity. These findings suggest that optimizing MT application can be an effective strategy to mitigate cadmium toxicity in soybean cultivation.